ANALISIS PERAN KADER TERHADAP CAPAIAN IMUNISASI DASAR LENGKAP DI WILAYAH KERJA PUSKESMAS JADDIH-SOCAH - Jannah, Raudatul; Retno Wati, Dwi; Tri Sumini, Gempi; Endah Pratiwi, Widhya; Sulianto, Bagus (LPPM STIKES HUSADA JOMBANG, 2024)
Immunization is an effort to actively generate or increase a person’s immunity against a disease so that he will no get sick or only get a mild illness. Based on the results of brief observations made at the Jaddih Health workers to get immunized, but only a small proportion of them understand immunization. Various reasons, ranging from not understanding the benefits of immunization to forgetting the next immunization schedule and many more. The purpose of this study was to determine the role of cadres in achieving complete basic immunization in Jaddih Village. This research method is correlation analysis with cross sectional approach. The independent variable is the achievement of complete basic immunization the total population is 30 respondents, the number of samples is 30 respondents. Sampling total using total sampling. The instrument used is a questionnaire. Statistical test using chi square with a significance value of α 0,05. The results of chi square statistical test for the role of cadres on the achievement of complete basic immunization obtained a ρ value of 0,001 < α 0,05 with indication a relationship between the role of cadres on the achievement of complete basic immunization in Jaddih Village. The role of Posyandu cadres in one of the important factors in immunization activities the role of cadres in necessary so that activities can run on a predetermined schedule. It can be seen thet cadres play an active role in Posyandu activities, including remiding parents